Pertanggungjawaban Hukum Penjual Atas Objek Jual Beli Yang Dijadikan Agunan Pembiayaan Perbankan (Studi Putusan Nomor 21/Pdt.G/2024/PN Pwr) - Ummu Aziizah; Sapardiyono Sapardiyono (Perkumpulan Maju Karya Yogyakarta, 2026)
This study aims to analyze the legal liability of sellers regarding objects of sale and purchase that are used as collateral in banking financing, as well as the legal consequences for the parties involved, based on Decision Number 21/Pdt.G/2024/PN Pwr. The issue arises from the seller’s action of pledging an object that has already been transferred to the buyer, resulting in a legal conflict between a good faith buyer and the bank as the creditor. This research employs a normative legal method with statutory, case, and conceptual approaches. The legal materials used consist of primary legal sources in the form of laws and regulations as well as court decisions, and secondary legal sources including literature and expert opinions. The results show that the seller’s actions constitute both a breach of contract and an unlawful act. The seller is liable for the losses suffered by the buyer, both material and immaterial. Furthermore, the security right imposed on the object is declared legally defective as it was executed by a party who no longer had authority over the object. The court decision also emphasizes that a good faith buyer must be given priority legal protection. Therefore, this decision reflects the application of the principles of justice, harmony, and expediency, and provides legal certainty for buyers in disputes concerning sale and purchase and financing.